Dinamika Kebijakan Keterwakilan Perempuan Pasca Reformasi Di Dewan Perwakilan Rakyat Republik Indonesia (DPR-RI) (Faculty of Communications Science, Dr. Soetomo University, 2022)
The background of this research is the phenomenon of female minority groups in the Indonesian parliament DPR-RI. The formulation of the problem that arises is how is the representation of women in the post-reform parliament? This research uses political recruitment theory and party typology. This study uses a qualitative method of library research, especially previous studies. This study finds women's affirmation policies have been present in the post-referral election law. However, the implementation of the rules is still not effective in increasing the number of women representatives at the national level of the DPR-RI. Several inhibiting factors; First, the 30 percent quota regulation for women in political contestation is still a nomination. Second, the dominance of party elite decisions with a patriarchal mindset is often an obstacle that hinders women's political participation. Third, the pattern of party recruitment tends to be pragmatic in the nomination of cadres as candidates for legislative members.